Peran Guru IPS dalam Meminimalisasi Risiko Negatif Media Sosial Tiktok pada Siswa Kelas VIII MTs Darul Falah Sumbergempol - Moh. Afini Maulaya; Yudi Krisno Wicaksono (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to investigate the role of social studies teachers in mitigating the negative impacts of TikTok usage among eighth-grade students at MTs Darul Falah Sumbergempol. With the rapid rise of social media use among adolescents, platforms like TikTok pose both opportunities and challenges, especially within educational and religious environments such as madrasas. A descriptive qualitative approach was adopted in this study, utilizing data collection techniques such as observation, interviews, and documentation. The research subjects included social studies teachers and eighth-grade students who were active users of TikTok outside school hours. Findings revealed that the majority of students used TikTok extensively in their free time, often engaging in content consumption and trend participation for prolonged periods. The negative risks identified included a decline in academic focus, adoption of slang and behaviors inconsistent with madrasa values, and increased susceptibility to peer pressure. In response, social studies teachers played a pivotal role in addressing these issues by integrating digital literacy concepts into classroom instruction, promoting the creation of positive and educational content, and fostering open communication with parents to monitor usage outside school. These strategies contributed to increased student awareness of the potential harms of uncritical social media use. However, the study also highlighted ongoing challenges, such as institutional gadget restrictions in Islamic boarding school environments and the extended duration often required to shift entrenched behaviors and digital habits. The study concludes that social studies teachers, when supported by a collaborative framework involving parents and school policies, can significantly influence students' digital behavior. Strengthening media literacy education and promoting critical thinking are essential steps toward cultivating responsible and ethical social media use among adolescents in religious educational settings.